APPROACHES TO TEACHING FOREIGN LITERATURE IN A FOREIGN LANGUAGE CONTEXT (Scientific journal of the Fergana State University, 2025)
The article discusses issues of applying approaches to teaching literature in a foreign language in order to find a solution for the proper organization of lectures, seminars and classroom lessons in literature with approaches that can meet the needs of students.